Challenges and Opportunities for Sharing Threat Information with Radioactive Materials Operators - Raphael Duguay (International Journal of Nuclear Security, 2020)
Operators are required to implement security measures to address requirements set by the regulatory body or competent authority. These security requirements are generally based on the national threat level and information provided by the relevant law enforcement authority, intelligence agencies and other relevant stakeholders. However, not all States can share this information with radioactive materials holders (e.g., operators), especially if they take a more prescriptive approach to regulation on security. The same situation often exists when a performance-based approach is used because there are multiple barriers that restrict the competent authority from sharing threat information. For example, competent authorities need to protect confidentiality and comply with national laws, regulations and other information security considerations. In this paper, the author presents some challenges and opportunities relevant to exchanging threat information. The objective is to reflect on current practices including good practices at the State and operator levels to facilitate cooperation between regulatory bodies and operators. The purpose is to increase awareness about the threats and techniques used by the adversaries and to assist stakeholders in maintaining vigilance without compromising the security and confidentiality of the information.
Keywords: security of radioactive materials; nuclear security information